Pengorganisasian Kegiatan Ekstrakurikuler Bahasa Arab di Madrasah Nurul Ulum Malang - Abdullah, Alfi Nur Azizah (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
The purpose of this research is to find out: 1) Organizing extracurricular activities in Arabic in Madrasah Nurul Ulum Malang, and 2) Constraints faced and the benefits they experience in organizing extracurricular activities in Arabic at Madrasah Nurul Ulum Malang. This study uses a descriptive qualitative research method. The data obtained is the organizational structure and the division of duties of each member of the organization, organizational instruments, extracurricular activity programs or fields, and the achievements of the students. The data sources were the manager of extracurricular activities and several members of the extracurricular activities organization. The data were collected by means of interview, observation, and document analysis techniques. After the data was collected, data analysis was carried out with the following stages: 1) data reduction, 2) data presentation, and 3) drawing conclusions. Organizing extracurricular activities cannot be said to be good because there is no permanent organizational pattern and does not yet have a standard organizational structure and assignments for each member of the organization. Apart from the shortcomings that teachers and students have, there are many benefits that can be felt by teachers and students from organizing extracurricular Arabic language activities at Madrasah Nurul Ulum Malang. Among them are the increased demand for students for extracurricular activities in Arabic, the increase in the achievement of Nurul Ulum madrasa students in the field of Arabic, and the emergence of new talents in the Arabic language.